ANALISIS PENDAPATAN BUDIDAYA BANDENG KELURAHAN TUGUREJO KECAMATAN TUGU KOTA SEMARANG - Hasan Faiq; Dewi Hastuti; Lutfi Aris Sasongko (Universitas Wahid Hasyim, 2012)
This research aims to determine the cost of production, revenue and income milkfish cultivation, and the factors that effect the cultivation of milkfish income Tugurejo Village Tugu District Semarang City. The sampling technique used purposive sampling methods, sampling of respondent was conducted by a simple random sampling. The population saple was taken by 45 respondents farmers cultivating milkfish population residing in the village Tugurejo. Methods of data collection through interviews, records, observations dan questionnaires. The results income from milkfish cultivation is to use the difference between total revenue (TR) and total cost (TC). With the average number of explicit costs of Rp 6.231.245 per season and the average numver of milkfish cultivation receipts in a production process of Rp 9.096.948 per season. Then obtained the average land area of 2,69. Value of R/C milkfish cultivation farm in thevillage Tugurejo was 1,62. The analysis of data by multiple linear regression. It is known that the free variables of land area (X1), seeds (X2), production cost (X3), total production (X4), and the selling price (x5), has been associated with variable tied to the level of milkfish cultivation income (Y). coefficient of determination (R2) 0,986 states the ability of the modl established by the independent variables in explaining the diversity of the dependent variable is equal to 98,6 percent, while the remaining 1,4 percent is explained by other variables. The land area variable has a p-value 0,337 > 0,05, meaning there is no significant influence of the land area to the income of milkfish cultivation. The seed variable has p-value 0,123 > 0,05, meaning there is no significant effect of seed for milkfish cultivation income result. The cost variable of production has p-value 0,000 < 0,01, mean very significant. The amount production variable has p-value 0,000 < 0,01, mean very significant. The selling price variable has p-value 0,000 < 0,01, mean very significant. Keywords : income, milkfish cultivation